Pré-processamento de modelos tridimensionais de veículos para uso em dinâmica de fluidos computacional - Medeiros, Igor Luiz Gomes de (Universidade Federal Rural do Semi-Árido, 2020)
Computational fluid dynamics (CFD) is a numerical simulation technique that has been applied to complex problems that offer difficulties in obtaining an analytical solution, in addition to being related to resource savings in fluid mechanics projects. With these advantages, the recent growth in the application of this technique is remarkable. The first stage of DFC is the pre-processing, which aims to adapt the mesh to facilitate the next stages of the project. By simplifying the mesh, the probability of a numerical error decreases. In this work, a systematic research on three-dimensional models of vehicles was performed, where several combinations of simplification and mesh subdivision were used, in order to obtain a better average quality of the triangles that make up the mesh. According to the data obtained, a set of procedures leading to a better quality of mesh was selected according to two criteria. The proposed technique can be valuable in the application of the DFC in cases where high processing power is not available.
Keywords: Dinâmica de fluidos computacional; Geração de malha; Triangulação; Túnel de vento; Computational fluid dynamics; Mesh generation; Triangulation; Wind tunnel; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA